Nanomaterials for diagnosis, treatment, and prevention of human cutaneous leishmaniasis: A review - Daniela Maza Vega; Magalí Di Meglio; Silvia del Valle Alonso; Fernando Alvira; Jorge Montanari (Elsevier, 2023)
Leishmania parasites are the organisms responsible for one of the most important tropical diseases, leishmaniasis. This neglected disease mainly affects populations in developing or underdeveloped countries, causing nearly one million new cases per year. This article focuses on the cutaneous form of the disease. Common antileishmanial medications have several disadvantages, such as low efficiency, high toxicity, several adverse effects, resistant strains, long treatments, and high costs. As a result, first- and second-line treatments are insufficient. Therefore, there is a need for new antileishmanial agents and strategies, most of which utilize nanotechnology. While novel nano-drug delivery devices can transport antileishmanial drugs to target cells, reducing secondary toxic effects, several advances in nanotechnology and photonics pursue activation of leishmanicidal mechanisms once they reach their target. Here is a summary of recent nanotechnology approaches to the treatment, diagnosis, and prevention of human cutaneous leishmaniasis, including promising techniques still in development.